(untitled) (Global Journal of Science Frontier Research, 2023)
The investigation had objective to reproduce on tubetes the species Sporobolus virginicus, as plantation material for dune ecosystems benefitted with sand dumpings. The variables evaluated were: sprouting percentage, height, number of leaves and number of sprouts. Three substrates (sand, sand+humus and worm humus) was evaluated. In the substrate with more sprouting percentage was evaluated the position of the rhizome segment (horizontal, vertical and in angle of 45°), the angle formed in the cut (90° and 45°), the viability at 24 o’clock, 48, 72 and 96 hours from its prospecting and the survival post-transplant. The rhizomes planted in humus did not sprout. The biggest sprouting percentage with 37% was obtained in the compound by the mixture of sand and humus. The horizontal position of the segments of rhizomes in the tubetes reached the biggest values for the evaluated variables and the number of final sprouts duplicated the vegetable established material initially. The position forming angle of 45° showed increment in the number of sprouts until the 64 days.